2006
DOI: 10.1111/j.1398-9995.2006.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum‐induced basophil CD63 expression by means of a tricolour flow cytometric method for the in vitro diagnosis of chronic urticaria

Abstract: Chronic urticaria serum-induced CD63 expression assay performed on DA whole blood by means of our tricolour FCM method could be the most useful tool for identification of a subset of patients with autoimmune CU and may become a promising tool also for monitoring treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 27 publications
4
39
0
Order By: Relevance
“…Our study is one of the first to compare CD63 and CD203c expression in a group of CU patients. Based on experience of other authors, who demonstrated that atopic donor basophils showed marked upregulation of CD63 and CD203c molecules after stimulation with serum from CU patients in this study we used highly atopic donor basophils [12,14,15]. Our study confirmed that serum from patients with CU, but not control sera, on average significantly upregulated atopic donor basophil CD63 and CD203c expression.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Our study is one of the first to compare CD63 and CD203c expression in a group of CU patients. Based on experience of other authors, who demonstrated that atopic donor basophils showed marked upregulation of CD63 and CD203c molecules after stimulation with serum from CU patients in this study we used highly atopic donor basophils [12,14,15]. Our study confirmed that serum from patients with CU, but not control sera, on average significantly upregulated atopic donor basophil CD63 and CD203c expression.…”
Section: Discussionsupporting
confidence: 74%
“…After ROC curve analysis, we concluded that CD203c did not have sufficient diagnostic power. Other authors, who tested CD63 [11][12][13][14][15] or CD203c expression [17] in CU patients, found significant correlation between ASST and both basophil activation tests positivity. The discrepancy between CD63 and CD203c correlations with ASST in our study can reflect either different mechanism of CD63 and CD203c molecules upregulation or differences in methodology of tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basophil histamine release assay (HRA) is currently the "gold standard" for detecting functional antibodies in the serum of patients with CU [5][6][7]. Improved screening tests have been sought in the last decade; for instance, flow cytometry used to determine the ability of a CU patient's serum to evoke an expression of CD63 and CD203c on donor basophils is showing some promise [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%